Tingkat Persepsi Mahasiswa Terhadap Kota Jambi Sebagai Kawasan Tanpa Asap Rokok (Peraturan Daerah Nomor 3 Tahun 2017) - Supeno Supeno; Fachruddin Razi; Mhd Ansori; Dedy Syaputra (Universitas Batanghari Jambi, 2021)
Non-Smoking Areas stipulates that non-smoking areas include public places, workplaces, places of worship, playgrounds, public transportation, teaching and learning process environments, health facilities and sports facilities, but in reality there are still many people who violate these provisions, including educated circles such as lecturers, teachers, students and so on. The purpose of this study was to obtain information about the level of educated people's perceptions of Jambi City as a smoke-free area and want to measure the participation of educated people in making Jambi City a smoke-free area. as the primary data source is the source of data obtained from interviews with selected samples and while the secondary data sources are books and journals and other research results, the approach used is the sociological aspect approach, namely to reveal social phenomena and phenomena that occur in the community. the field, while the data collection technique used is interview technique, the sampling technique is done by random sampling and purposive sampling, the data used is qualitative data, the results of the study show that the level of student knowledge Wa about Jambi City as a smoke-free area is quite good and optimistic about the implementation of Jambi City as a smoke-free area.